TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE: AN OVERVIEW & LOOK TOWARD 990000 990121 (Tufts Archival Research Center, 2007)
Tobacco Industry Labor Management Committee (LMC) overview & look towards 1999. Discusses the success of the LMC to date and its allies. Lists goals for 1999. Summarizes direct lobbying activities and legislative support. Outlines special projects. Describes committee staff and administrative support. Itemizes LMC costs.